2016
DOI: 10.1021/acs.est.5b06388
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Biodegradation of Alternative Fuels and Associated Biocorrosion of Carbon Steel in Marine Environments

Abstract: Fuels that biodegrade too easily can exacerbate through-wall pitting corrosion of pipelines and tanks and result in unintentional environmental releases. We tested the biological stability of two emerging naval biofuels (camelina-JP5 and Fischer-Tropsch-F76) and their potential to exacerbate carbon steel corrosion in seawater incubations with and without a hydrocarbon-degrading sulfate-reducing bacterium. The inclusion of sediment or the positive control bacterium in the incubations stimulated a similar patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…incubations (Liang et al 2016a). While the corrosion rates detailed in this study were 607 comparable or slightly higher than those observed previously (Liang et a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…incubations (Liang et al 2016a). While the corrosion rates detailed in this study were 607 comparable or slightly higher than those observed previously (Liang et a.…”
mentioning
confidence: 99%
“…In addition, the environmental release of fuels is sometimes associated with the 79 biocorrosion of the carbon steel infrastructure. Fuels that biodegrade too easily serve as 80 carbon and energy sources for the proliferation of microbial communities that ultimately 81 exacerbate biocorrosion through-wall pitting corrosion of pipelines, tanks and other 82 equipment (Aktas et al 2010, Lenhart et al 2014, Liang et al 2016a). Concomitant with 83 the introduction of ULSD were increased reports of infrastructure corrosion (Anonymous, 84 2012).…”
mentioning
confidence: 99%
“…It is generally acknowledged that sulfate-reducing bacteria have major responsibility for MIC in anoxic environments (e.g., buried petroleum pipelines), and carbon steel or iron corrosion was observed to positively correlate with sulfate loss in incubation media. 36,37 Based on this, signicantly lower sulfate contents in C-soil and O-soil samples could be a sign of pipeline corrosion and the pipeline surrounded by C-soil endured more severe corrosion, as their sulfate content was the lowest (Table 1). Taken together, from the microbial community composition and LEfSe analysis, Balneolaceae genera (Balneola and KSA1), Flavobacteriaceae genera (Muricauda and Gramella), and Desulfuromonadaceae genera (Pelobacter, Geoalkalibacter) were signicantly more abundant in the C-soil population (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Hydrogen sulide also dissolves in the fuel and the fuel can become aggressive toward steel, silver and copper alloys [31]. Anaerobic bacteria are a particular problem in marine environments where salt water provides an abundant supply of sulfate that the anaerobic bacteria convert to hydrogen sulide which leads to foul smelling and toxic fuel and signiicant biocorrosion of steel [32].…”
Section: Flight Physics -Models Techniques and Technologies 202mentioning
confidence: 99%